2017
DOI: 10.1111/jocd.12373
|View full text |Cite
|
Sign up to set email alerts
|

Potential emerging treatment in vitiligo using Er:YAG in combination with 5FU and clobetasol

Abstract: Greater reduction in the size and increase in pigmentation score was seen in Er:YAG group especially for short periods after therapy and repeating laser sessions may help improving final outcomes. Er:AYG could help in reducing complications of long-term topical treatments, achieving faster response, and improving patient adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Another study by Anbar et al 24 used Er:YAG laser followed by topical 5‐FU and NB‐UVB on one side of the body versus NB‐UVB only on the other side, and reported moderate to marked repigmentation response in the side treated with Er:YAG laser followed by topical 5‐FU and NB‐UVB in (78.1%) of patients. These differences in repigmentation response between the above‐mentioned studies, 24,29‐33 and the current work could be attributed to different types of lasers used, the number of laser sessions, laser parameters, or the use of a third line of therapy as topical combinations with 5‐FU like clobetasol, 33 or narrow‐band ultraviolet B (NB‐UVB) 24 . Although the studies that used Er:YAG laser demonstrated promising results, 24,32,33 they reported difficulty in precising the resurfacing depth, and liability for scarring as a result of excessive injury in some cases 24,32,33 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Another study by Anbar et al 24 used Er:YAG laser followed by topical 5‐FU and NB‐UVB on one side of the body versus NB‐UVB only on the other side, and reported moderate to marked repigmentation response in the side treated with Er:YAG laser followed by topical 5‐FU and NB‐UVB in (78.1%) of patients. These differences in repigmentation response between the above‐mentioned studies, 24,29‐33 and the current work could be attributed to different types of lasers used, the number of laser sessions, laser parameters, or the use of a third line of therapy as topical combinations with 5‐FU like clobetasol, 33 or narrow‐band ultraviolet B (NB‐UVB) 24 . Although the studies that used Er:YAG laser demonstrated promising results, 24,32,33 they reported difficulty in precising the resurfacing depth, and liability for scarring as a result of excessive injury in some cases 24,32,33 .…”
Section: Discussionmentioning
confidence: 68%
“…These differences in repigmentation response between the above‐mentioned studies, 24,29‐33 and the current work could be attributed to different types of lasers used, the number of laser sessions, laser parameters, or the use of a third line of therapy as topical combinations with 5‐FU like clobetasol, 33 or narrow‐band ultraviolet B (NB‐UVB) 24 . Although the studies that used Er:YAG laser demonstrated promising results, 24,32,33 they reported difficulty in precising the resurfacing depth, and liability for scarring as a result of excessive injury in some cases 24,32,33 . Moreover, FrCO 2 laser was studied in combination treatments for vitiligo, with NB‐UVB therapy, sun exposure, and also with topical agents like corticosteroids or salicylic acid that get the benefit of synergism and avoid the disadvantages of Er:YAG laser 34‐36 …”
Section: Discussionmentioning
confidence: 68%
“…They found better response at the medium or high energy protocols [41]. Mohtari et al tried to find a unresponsiveness vitiligo part a new modality that is firstly used ER:YAG laser than applied clobetasol or 5-FU dressing and found better cosmetic results via ablation [42]. As expected, periungual vitiligo hard places to treat responded well.…”
Section: Erbium Laser For Ablation Modalitiesmentioning
confidence: 88%
“…18 The current study comes in line with the other studies documenting the efficacy of combining ablative methods with conventional modalities in the treatment of vitiligo. [12][13][14][15] However, some of these ablative modalities might carry the risk of delayed healing and scarring like in Er:YAG laser 12 or may be associated with difficulty in controlling the depth of ablation like in dermabrasion with possible koebnerization. 15 with traditional laser resurfacing.…”
Section: Discussionmentioning
confidence: 99%